Influence of board diversity on the financial performance of commercial banks in Kenya - Wambui, Kaguongo (Strathmore University, 2018)
This study’s purpose was to explore the effect of board diversity in leadership on corporate financial performance. Specifically, the study aimed at determining the effect of board diversity on financial performance of commercial banks in Kenya to ascertain whether there is a causal association between the specific board characteristics of gender, age and nationality on the financial performance of commercial banks in Kenya. Thus, the research adopted an exploratory design. All commercial banks formed the primary target in the study. There were forty-two banks in Kenya based on the 2017 Bank Supervision Report by the CBK (Central Bank of Kenya). Pertinent data in the study was sourced from secondary sources. Panel data regression analysis was applied to ascertain the association between board diversity and financial performance of the commercial banks. The study results indicated that board age diversity did not have a significant effect on financial performance measured through ROA and Tobin’s Q. Similarly, gender diversity had insignificant effect on financial performance of the commercial banks in Kenya measured through both ROA and Tobin’s Q. Further, nationality diversity was not significantly related with financial performance of the commercial banks as measured through both ROA and Tobin’s Q. Study results also indicated that board diversity (BD) did not have a significant effect on ROA as well as Tobin’s Q of the commercial banks. The recommendations made from these findings is that when selecting boards members, shareholders should consider having a board that is composed of members from different ethnic, cultural, gender and nationalities which is expected to provide a diverse view of managerial and strategic issues. However, diversity should not only be considered for its own sake but should be considered on how well it will enhance the board leadership and control role in the firm. The study also recommends to the shareholders of companies to ensure that demographic diversity is informed by the interests of the companies, and not just for the sake of having a demographically diverse board.
Submitted in partial fulfillment of the requirements for the Master of Business Administration at Strathmore University
Keywords: Corporate Financial Performance; Board diversity; Central Bank of Kenya